Electrochemical epitaxial PbTe nanowires photodetector for NIR response. (26th November 2022) - Guo, Zhongmin; Zhang, Zhisheng; Yan, Ruiyang; Feng, Shuanglong
Abstract: Lead telluride nanowires deposited by electrochemical atomic layers have broad application prospects in the field of photodetectors. In this work, using the method of electrochemical atomic layer deposition, we obtained different morphologies of lead telluride materials by controlling the deposition parameters, such as deposition time, temperature, and potential, and characterized them using SEM, TEM, XPS, and other techniques. A lead telluride nanowire detector with good performance was prepared. The photoresponsivity of the detector is 102 mA W −1, the detectivity is 2.1 × 10 8 Jones, and the response time and recovery time are 0.52 s and 0.54 s respectively at 2.7 μ m wavelength laser irradiation.